Impact of COVID-19 on the Delivery of Eye Care to Uninsured Diabetic Patients at a Student-Run Free Clinic: A Comprehensive Evaluation of Eye Clinic Performance - Chuter, Benton; Lieu, Alexander; Dayao, John Kevin; Bu, Jennifer; Chen, Kevin; Nishihara, Taiki; Baxter, Sally (Journal of Student-Run Clinics, 2022)
Background: Diabetic retinopathy is the leading cause of blindness among working-age adults in the United States and requires timely screening and management. This study evaluates the impact of the coronavirus disease 2019 (COVID-19) pandemic on diabetic retinopathy screening (DRS) for uninsured, predominantly Latino patients at the University of California San Diego Student-Run Free Clinic Project (SRFCP). Methods: A retrospective chart review was conducted of all living diabetic patients at SRFCP who were seen in 2019 (n=196), 2020 (n=183), and 2021 (n=178). Ophthalmology clinic referrals, scheduled patient visits, and visit outcomes were analyzed longitudinally to determine the impact of the pandemic on screening patterns. Results: The study population was 92.1% Latino, 69.5% female, with a mean age of 58.7 years. The distribution of patients seen (p<0.001), referred (p=0.012), and scheduled (p<0.001) in 2020 and 2021 significantly differed from 2019. In 2019, 50.5% of 196 patients eligible for DRS were referred, 49.5% were scheduled, and 45.4% were seen. In 2020, 41.5% of 183 eligible patients were referred, but only 20.2% were scheduled and 11.4% were seen. In 2021, there was a rebound: 63.5% of 178 patients were referred, 56.2% scheduled and 46.1% seen. No shows and cancellations represented 12.4% and 6.2% of the 97 encounters scheduled in 2019, but were markedly higher (10.8% and 40.5% respectively) for the 37 encounters scheduled in 2020. Conclusions: The COVID-19 pandemic significantly impacted the delivery of eye care at SRFCP. The need for annual DRS exceeded the capacity of the ophthalmology clinic in all years studied, but the difference was especially pronounced with more stringent COVID-19 restrictions in 2020. SRFCP patients could benefit from telemedicine DRS programs to improve screening capacity.